Peranan Tenaga Kerja Keluarga Dalam Usaha Pemeliharaan Sapi di Kabupaten Tanjung Jabung Barat - Darmawi, Darlim (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2012)
This research  aims to determine the role of family labor in its economic contribution to devote time and efforts on raising cattle. Methods This research uses survey methods. Object of research is the Bali cattle ranchers in the farmer groups in the village of Bright Surya Jaya Regency Tanjung Jabung Makmur West. Respondents of this  research  of 12 families who acquired purposive sampling, with the following criteria: cattle that are a venture capital fund amplifier (PMU) (first-year period 2006-2010), a semi-intensive system maintenance and return patterns of a back one. The analysis used is deskriptiv analysis. To find the outpouring of work hours is to use the calculation of the number of hours worked in the maintenance of the outpouring of cattle based on equality unit of Manpower Equivalent Man (TKSP). Contribution of labor in the calculation of income from cattle using analysis of percentage (%). While the analysis of income from cattle using analysis of income. Results of analysis showed, that the maintenance of cattlefrom 12 families (100%) is still a side business, including the category of the pattern of family farming, with cattle ownership on average 4.63 ST / breeder. In maintaining cattle ranchers are still in the average age of 45.08 (25-60) years including labor that is still productive age, and can devote his time of 3.9975 million JKP / period, the economic value of Rp.199.837.500, - / period. While revenues without raising cattle farmer labor contribution is Rp. 185 640 925,-period, so the total revenue obtained from rearing cattle is Rp. 385,478,425, -/periode. Based on the analysis of the value of the economic contribution of labor in cattle revenues amounted Rp.199.837.500, -/periode or for 51.84% of total revenue. Thus the contribution of labor income of beef cattle farmers in the relatively larger than the non-contribution income cattle labor by 48.16% of the total income of cattle.